Applying neoteric MgTiO3-coated TiO2 nanoparticulate films as scaffold layers in perovskite solar cells based on carbon counter electrode for retarding charge recombination. (1st April 2020) - Zhang, Bowen; Zhang, Bo; Wang, Shaowei; Yao, Shujuan; Bala, Hari; Sun, Guang; Cao, Jianliang; Zhang, Zhanying
Abstract: MgTiO3 -coated TiO2 mesoporous scaffold layers were fabricated and applied in perovskite solar cells (PSCs) based on carbon counter electrode (CCE), in which TiO2 mesoporous layers were treated with different concentration of Mg 2+ solution. Compared with PSCs based on pure TiO2 mesoporous layer, the open circuit voltage ( V oc ) and circuit photocurrent density ( J sc ) of MgTiO3 /TiO2 -based devices significant improved. Intensive characterizations including scanning electron microscopy, electrochemical impedance spectroscopy can confirm that the presence of MgTiO3 shell layer can't only retard charge recombination at CH3 NH3 PbI3 /TiO2 interface, but also have a strong effect on the perovskite film growth. Based on the optimized treating concentration of 0.10 M, power conversion efficiency (PCE) of 10.39% could be achieved for the hole-conductor-free PSCs with excellent long-term stability, suggesting immense potential for large-scale industrial production in the future. Graphical abstract: Image 10988843 Highlights: MgTiO3 -coating TiO2 mesoporous layers were fabricated and applied in PSCs. Carbon replaces the noble metal as counter electrode for saving cost. MgTiO3 shell can retard charge recombination in PSCs. The optimized devices show high V oc of 0.95 V and PCE of 10.39%. The PSCs exhibited excellent long-term stability under high humidity of ∼50%.